Credit Risk, Credit Rationing, and the Role of Banks: The Case of Risk Averse Lenders - Thilo Pausch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
The standard situation of ex post information asymmetry between borrowers and lenders is extended by risk aversion and heterogenous levels of reservation utility of lenders. In a situation of direct contracting optimal incentive compatible contracts are valuable for both, borrowers and lenders. However, there may appear credit rationing as a consequence of borrowers optimal decision making. Introducing a bank into the market increases total wealth due to the appearance of a portfolio effect in the sense of first order stochastic dominance. It can be shown that this effect may even reduce the problem of credit rationing provided it is su?ciently strong.
urn:nbn:de:bvb:384-opus4-711838
Keywords: L22; G21; D82; 330; risk aversion; costly state verification; credit rationing; bank